Taekwon-do: a chance to develop social skills - Ortenburger, Dorota; Wasik, Jacek; Gora, Tomasz; Tsos, Anatolii; Bielikowa, Natalia (My University, 2017)
Background. Social skills contribute to the proper functioning of an individual in the social environment. Not only in the case of people’s cooperation, but also when we consider competing. The programmes, supporting the development of the models of human behaviour, are still being searched. That is why, the aim of the research is the knowledge concerning the impact of taekwon-do training on the development of different social skills. Method. The research covered 31 people practising taekwon-do, 17 men and 14 women (age:18.83±3.49 years old; range: 16-28 years old) in ITF taekwon-do clubs. The measurement was performed with the use of the Personal Competence Scale (of the results ranging between 12 and 48) and with the use of a self-made questionnaire. In the conducted research, for all registered indexes, the median (SR), variance (SS) and standard deviation (SD) were indicated. The correlation between the selected indexes was indicated. The variance analysis ANOVA was conducted. The statistical validity was assumed at the level of p<0.05. Results. The following indexes were registered: the average value of the subjectively assessed increase of self-esteem in the situation of social exposure: women 6.00±2.60 (level 1-10), men 8,94±1.14 (level 1-10); the average degree of satisfaction with social contacts, based on sharing sport interests: men 8.76±0.75 (level 1-10), women 8.64±.0.74 (level 1-10); value of the index of the feeling of personal competence at men 36.35±7.04 (level 12-48); women 31.86 ±8.47 (level 12-48). Conclusion. In the whole group, the increase of self-esteem in the situation of social exposure was revealed- higher in the case of men than women. The level of satisfaction, due to the increase of social contacts based on sharing sport interests at women and men, did not differ. The feeling of personal competence in the researched group is higher in the case of men than women that can be interpreted based on cultural and biological conditions. Taekwon-do competitors indicate the effects that facilitate functioning in the social life, that result from practicing martial arts.
Keywords: social skills; the feeling of competence; adolescence; taekwon-do; social exposure; reference group; sharing interests